(untitled) (Journal of Scientific Research, 2020)
The primary intend of this article is to define a new class of mappings called Ng# α-quotient mappings in nano topological space. The intention is to analyze characterizations and inter relationship of Ng# α-quotient mappings with nano Tg#α-space, Ng# α-continuous, Ng# α-open, Ng# α-irresolute, Ng# α-homeomorphism and nano α-quotient mapping. Also several properties of strongly Ng# α-quotient mapping are derived and the relationships among them are illustrated with the help of examples. Their interesting composition with strongly Ng# α-irresolute are established. The concept of Ng# α-quotient mapping is explored and composition of mappings under strongly Ng# α-quotient mapping and Ng# α-quotient mapping are discussed. Furthermore, to emphasize Ng# α-quotient mapping a few examples are considered and derived in detail.